ChemInform Abstract: Palladium‐Catalyzed Air‐Based Oxidative Coupling of Arylboronic Acids with H‐Phosphine Oxides Leading to Aryl Phosphine Oxides. Issue 44 (4th November 2014) - Fu, Tingting; Qiao, Hongwei; Peng, Zhimin; Hu, Gaobo; Wu, Xueji; Gao, Yuxing; Zhao, Yufen
Abstract A novel methodology for the creating C—P bond via the oxidative coupling of a wide range of arylboronic acids with various H‐phosphine oxides in the presence of palladium catalyst under dry air as the green oxidant is described.